The Effect of Green Value, Environmental Commitment, and Social Influence on Green Purchase Intention For Environmentally Friendly Skincare Products (Nature Republic) - Putri Ameliya Bahari; Muh Santoso (Dinasti Review, 2026)
The increasing public awareness of environmental issues has contributed to the growth of environmentally friendly consumption behavior, including the intention to purchase green products. This study aims to analyze the influence of Green Value, Environmental Commitment, and Social Influence on Green Purchase Intention using a quantitative survey approach involving 200 respondents, with data analyzed through multiple linear regression using SPSS. The results indicate that Green Value, Environmental Commitment, and Social Influence each have a positive and significant effect on Green Purchase Intention, both partially and simultaneously, while the coefficient of determination (R²) shows that most of the variation in Green Purchase Intention is explained by these variables, with the remainder influenced by other factors. These findings suggest that perceived environmental value, individual commitment to environmental sustainability, and social influence play crucial roles in shaping consumers' intention to purchase environmentally friendly products; Therefore, enhancing product environmental value, strengthening environmental commitment, and leveraging social influence are important strategies to promote sustainable consumption behavior.